A Comprehensive Quantitative Assay for Amine Transaminases. Issue 19 (6th September 2019) - Cairns, Ryan; Gomm, Andrew; Peel, Christopher; Sharkey, Michael; O'Reilly, Elaine
Abstract: The development of effective high‐throughput screening assays has contributed greatly to the wealth of designer enzymes available, by enabling rapid identification of desired variants from large mutant libraries. Here, we report a general and operationally simple end‐point assay for transaminases that enables the screening of both amine donors and acceptors in liquid phase. The spectrophotometric‐based screen exploits the amine donor 2‐aminoethylaniline (2‐AEA) and relies on reaction of in situ generated indole with Ehrlich's reagent. The assay has also been adapted to allow screening in the reverse direction by addition of indole and subsequent spectrophotometric analysis. Importantly, the screen provides qualitative information on the enantio‐preference of the individual biocatalysts. To increase the assay throughput, an engineered expression strain ( E. coli BL21(DE3) Δ tnaA ) lacking tryptophanase activity, was generated to enable reliable and direct evaluation of individual colonies arrayed on agar plates. Abstract : Simple and reliable : An operationally simple assay for transaminases is presented, which relies on reaction of in situ generated or exogenously added indole with Ehrlich's reagent. An engineered E. coli BL21(DE3) expression strain was developed to enable reliable and direct evaluation of individual colonies arrayed on agar plates.